1981
DOI: 10.1073/pnas.78.6.3950
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protein synthesis underlying functional plasticity in immature monkey visual system.

Abstract: Local rates of cerebral protein synthesis were determined in newborn rhesus monkeys subjected to either acute or chronic monocular visual deprivation. Chronic monocular deprivation resulted in decreased rates of protein synthesis in the laminae ofthe lateral geniculate nuclei innervated by the deprived eye whereas rates of protein synthesis were normal in geniculate laminae innervated by the functioning eye. Acute monocular deprivation produced no differential changes in rates ofprotein synthesis in any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Studies in rodents have demonstrated that rCPS changes during the process of aging (Ingvar et al , 1985) and during brain development (Sun et al , 1995). Activity-dependent protein synthesis is thought to be an integral step in many forms of synaptic plasticity (Nguyen et al , 1994), and, in a study of developmental plasticity in monkeys, we found regionally selective changes in rCPS (Kennedy et al , 1981). Variations in rCPS likely reflect adaptive processes taking place over a longer period of time compared with the acute physiological changes signaled by positron emission tomography (PET) measurements of regional cerebral metabolic rate for glucose or cerebral blood flow.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Studies in rodents have demonstrated that rCPS changes during the process of aging (Ingvar et al , 1985) and during brain development (Sun et al , 1995). Activity-dependent protein synthesis is thought to be an integral step in many forms of synaptic plasticity (Nguyen et al , 1994), and, in a study of developmental plasticity in monkeys, we found regionally selective changes in rCPS (Kennedy et al , 1981). Variations in rCPS likely reflect adaptive processes taking place over a longer period of time compared with the acute physiological changes signaled by positron emission tomography (PET) measurements of regional cerebral metabolic rate for glucose or cerebral blood flow.…”
Section: Introductionmentioning
confidence: 70%
“…The l -[1- 11 C]leucine PET method for the quantitative measurement of rCPS in human subjects provides us with a new and potentially powerful tool to investigate adaptive CNS responses in humans. In animal models, conditions such as sleep, hibernation, axonal injury with subsequent regeneration, synaptic plasticity in the visual system, and ischemia are all associated with altered rCPS compared with appropriate controls (Frerichs et al , 1998; Kennedy et al , 1981; Nakanishi et al , 1997; Smith et al , 1984; Widmann et al , 1991). The l -[1- 11 C]leucine PET method can be used to track changes in rCPS and/or Λ across regions and over time.…”
Section: Discussionmentioning
confidence: 99%
“…Further decreases occur during the more prolonged process of aging (Smith et al, 1995). Regional rates of cerebral protein synthesis are also affected by changes in synaptic input during development as seen in a study of plasticity in the developing monkey visual system (Kennedy et al, 1981). Studies in monkeys show a positive correlation between rCPS and deep sleep (Nakanishi et al, 1997), and during hibernation in ground squirrels rCPS is suppressed to less than 1% of normal (Frerichs et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream signaling events are not well understood, but the many instances of activity-dependent protein synthesis documented suggest that translation of proteins is required for normal plasticity. Multiple plasticity-related genes show visually driven increases in protein levels, including oCaMKII (Wu et al, 1998) and the calcium/cyclicAMP-response element binding protein (Pham et al, 1999), and lengthy MD can alter gross levels of protein synthesis in the lateral geniculate nucleus (LGN: Kennedy et al, 1981). Neurotrophins and their receptors are regulated in an activity-dependent fashion in vitro and in vivo (Zafra et al, 1992;Schoups et al, 1995;Androutsellis-Theotokis et al, 1996;Lein and Shatz, 2000) and have potent effects upon synaptic plasticity in the visual cortex (Cabelli et al, 1995;McAllister et al, 1995;Hanover et al, 1999;Gillespie et al, 2000).…”
Section: Resultsmentioning
confidence: 99%